PENYULUHAN TENTANG PENGGUNAAN MODEL PEMBELAJARAN THINK TALK WRITE PADA SISWA KELAS X SMK YAPIM BIRU – BIRU - Mona Fitri Gurusinga; Afrilius Simanjuntak (INSTITUT KESEHATAN DELI HUSADA, 2021)
This counseling purpose to know use of the Think Talk Write (TTW) Learning Model on Students' Ability to Write Persuasion Texts by Class X Students of SMK YaPIM Biru - Biru which consists of 7 classes with a total population of 240 students. From the determined population, 64 students were determined with a total of two classes selected by cluster sampling, namely class X 3 and class X 4. The data information technique used was normality test using the F test, homogeneity test and hypothesis testing using the